2009
DOI: 10.1007/s10482-009-9322-y
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of S-layer proteins from aggregating and non-aggregating Lactobacillus kefir strains

Abstract: Since the presence of S-layer protein conditioned the autoaggregation capacity of some strains of Lactobacillus kefir, S-layer proteins from aggregating and non-aggregating L. kefir strains were characterized by immunochemical reactivity, MALDI-TOF spectrometry and glycosylation analysis. Two anti-S-layer monoclonal antibodies (Mab5F8 and Mab1F8) were produced; in an indirect enzyme-linked immunosorbent assay Mab1F8 recognized S-layer proteins from all L. kefir tested while Mab5F8 recognized only S-layer prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 33 publications
(42 reference statements)
6
43
0
5
Order By: Relevance
“…The S-layer glycoprotein of Halobacterium halobium (salinarum) was the first published example of a prokaryotic glycoprotein (Mescher et al 1974). This led to a plethora of reports about S-layer glycoproteins in non-eukaryotes (Schaffer and Messner 2004) and recently, Mobili et al (2009) used periodic acidSchiff staining of polyacrylamide gel fractionated proteins to reveal that all extracted Lactobacillus kefir S-layer proteins were glycosylated (Mobili et al 2009). In addition to S-layer glycoproteins in bacteria, the pili and flagelli glycoproteins have also received a lot of attention.…”
Section: Glycosylation In Bacteriamentioning
confidence: 99%
“…The S-layer glycoprotein of Halobacterium halobium (salinarum) was the first published example of a prokaryotic glycoprotein (Mescher et al 1974). This led to a plethora of reports about S-layer glycoproteins in non-eukaryotes (Schaffer and Messner 2004) and recently, Mobili et al (2009) used periodic acidSchiff staining of polyacrylamide gel fractionated proteins to reveal that all extracted Lactobacillus kefir S-layer proteins were glycosylated (Mobili et al 2009). In addition to S-layer glycoproteins in bacteria, the pili and flagelli glycoproteins have also received a lot of attention.…”
Section: Glycosylation In Bacteriamentioning
confidence: 99%
“…In Grampositive pathogens, such as streptococci and staphylococci, several serine-rich fimbria-like adhesins undergo glycosylation (4,33,41). In lactobacilli, the only glycoproteins characterized to date are S-layer proteins, in addition to a peptide bacteriocin (27,29,44).…”
mentioning
confidence: 99%
“…Cell surface proteins extraction from LAB cells was performed using 5 M LiCl, as described in previous reports. 24,25) The cells removed surface protein were used in co-aggregation assay. The protein profile in the cell surface layer extracts was analyzed by sodium dodecylsulphate-polyacrylamide gel electrophoresis (SDS-PAGE), as described below.…”
Section: Methodsmentioning
confidence: 99%
“…9) There are other reports on the co-aggregation of LAB including Lactobacillus and yeasts including Saccharomyces. [10][11][12][13] Pretzer et al found that L. plantarum WCFS1 co-aggregates with yeast S. cerevisiae.…”
mentioning
confidence: 99%